Reducing Sodium Content in Cheeses While Increasing Salty Taste and Fat Perception Using Aroma - Syarifuddin, Adiansyah; Septier, Chantal; Salles, Christian; Thomas-Danguin, Thierry (Frontiers in Nutrition, 2022)
Excess salt (NaCl) and fat intake are major causes of chronic diseases, but reducing such components without affecting acceptability is a major challenge. Here, we set out to examine whether added aroma in lower salt real cheese can enhance saltiness and fat perception. Low-salt cheese samples were grated through a homogenizer, and then aroma solution, sardine aroma (salt-associated), butter aroma (fat-associated) and a mix of sardine and butter aromas were added. The results confirmed that grating changes cheese texture, leading to induced taste perception. In addition, a significant saltiness enhancement was induced by sardine aroma and to a lesser extent by butter aroma, while significant fat perception enhancement was only induced by blended aroma. These findings show that aroma addition can be a strategy to compensate for sodium reduction in commercial cheese. Concerning fat perception, the addition of aroma can be a good strategy to compensate for low-fat in commercial cheeses. However, the mechanisms involved seem complex and need to be elucidated.